2018
DOI: 10.1007/s40279-018-0874-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Dose–Response Relationships of Motor Imagery Practice on Strength Development in Healthy Adult Populations: a Systematic Review and Meta-analysis

Abstract: The present meta-analysis demonstrates that compared to a no-exercise control group of healthy adults, MI practice increases MVS, but less than PP. These findings suggest that MI practice could be considered as a substitute or additional training tool to preserve muscle function when athletes are not exposed to maximal training intensities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
92
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 126 publications
8
92
0
4
Order By: Relevance
“…Indeed, MI practice induces cortical reorganization [59]. Further, it evokes movement-related cortical potentials, enhancing corticospinal excitability and muscular activity, which that consequently leads to increased muscle force output [13,[60][61][62]. To the best of our knowledge, only one previous study tested the hypothesis that MI training increases voluntary neural drive to task-oriented muscle action assessed by the twitch interpolation technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, MI practice induces cortical reorganization [59]. Further, it evokes movement-related cortical potentials, enhancing corticospinal excitability and muscular activity, which that consequently leads to increased muscle force output [13,[60][61][62]. To the best of our knowledge, only one previous study tested the hypothesis that MI training increases voluntary neural drive to task-oriented muscle action assessed by the twitch interpolation technique.…”
Section: Discussionmentioning
confidence: 99%
“…Motor imagery (MI)-i.e., the mental representation of a physical action without overt body movement [11]-is effective in improving motor performance [12,13]. MI exerts beneficial effects on strength [13] and flexibility [14] in healthy adults; it reduces pain [15,16]; and it contributes to the rehabilitation of Parkinson's disease and stroke patients [17,18], though its effects on musculoskeletal patients are equivocal [19]. A recent metaanalysis showed that, when added to routine physical therapy (RPT) in post-injury rehabilitation, MI does not elicit greater benefits on functional mobility, perceived pain, and self-efficiency than RPT alone [19].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, motor imagery [MI] that refers to mental representation of an action without any concomitant body movement ( 7 ), is a widely used cognitive strategy to enhance functional performance for both sports-based ( 8 , 9 ) and therapeutic interventions ( 10 , 11 ). Hence, it shows a promising indication of implementation in the rehabilitation practice of orthopaedic ( 12 , 13 ) and Parkinson’s disease patients ( 11 ), following immobilization ( 14 ) or stroke rehabilitation ( 10 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowing that antagonistic muscle activity increases when the complexity of the movement rises (e.g., during closed chain, weight-bearing exercise), quadriceps function is more affected leading to greater difficulty in performing everyday activities such as walking or standing up from the chair, thus affecting patients' overall functionality and quality of life [57]. A recent comprehensive review of available literature found motor imagery (MI) practice to have moderate beneficial effects on strength gains, regardless of the cortical representation of trained muscle, suggesting that both large and small cortically represented muscles can almost equally benefit from MI practice [58]. The underlying mechanisms of the observed strength gains might be explained by alteration of both central and peripheral levels of muscle action control [59,60], with evidence of higher agonist activation [61] followed by antagonistic muscle inhibition during agonistic muscle action [62].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of the observed strength gains might be explained by alteration of both central and peripheral levels of muscle action control [59,60], with evidence of higher agonist activation [61] followed by antagonistic muscle inhibition during agonistic muscle action [62]. Therefore, incorporating MI practice in early stages of injury or surgical rehabilitation should be considered, when overt movement is restricted [50,58,61].…”
Section: Discussionmentioning
confidence: 99%